PERANAN DUKUNGAN NUTRISI TERHADAP PERUBAHAN STATUS ALBUMIN PADA PASIEN HIPOALBUMINEMIA RAWAT INAP DI RSUP DR SARDJITO YOGYAKARTA - , NIA TIFFANY HARKA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Incidence of protein energy malnutrition in internal medicine ward patients is still high. The prevalence of malnutrition increased from 46.7% to 50.7%. Albumin is one indicator of biochemistry to detect malnourished patients. Used as a nutritional support therapy beyond dietary therapy to overcome with inadequate intake of patients. So it is important to know the role of nutritional support to change the albumin status. Objective: To determine the role of nutritional support to change albumin status in hypoalbuminemia hospitalization patients. Methods: This study is an observational study with a nested case-control method that was conducted in March-August 2013 in the department of internal medicine wards Dr. Sardjito Yogyakarta. Sample size that met the inclusion criteria were 108 people. Determination the case-control group perfomed in the end of study. Cases were patients with albumin status change down, while controls groupwere patients with albumin status change remain/up. Food intake data obtained from recall and comstock, nutritional support data obtained from recall and comstock, interviews directly, and medical records. Weight and heigt data obtained through anthropometric measurements. Other data obtained from patient medical records. Data were analyzed by using chi-square test, t test, and Mantel haenzel test. Results: The results of chi square test showed that there was differences in protein energy intake in patients receiving nutritional support than no nutritional support. (Energy intake OR = 2.48